Serum metabolites with diagnostic potential in prostate cancer and the inhibitory effects of alpha-Tocomonoenol on prostate cancer cells - Shen, Yang; Liu, Bo; Zhou, Yuhua; Lv, Jing; Zhang, Xiang; Yang, Chun; Zhang, Yuwei; Feng, Ninghan (Frontiers in Oncology, 2025)
IntroductionProstate cancer is the most common malignant disease of the male urinary system, seriously endangering men’s health. Currently, early detection of prostate cancer mainly relies on prostate-specific antigen (PSA) screening; however, PSA is characterized by high sensitivity but low specificity. Patients with PSA levels in the gray zone (4-10ng/ml) are at risk of excessive medical interventions, highlighting the great significance of exploring new diagnostic indicators for prostate cancer.MethodsA total of 60 subjects were enrolled in this study, including 30 prostate cancer patients and 30 benign prostatic hyperplasia patients. Non-targeted metabolomics analysis was performed on the subjects, and the profiling results were statistically analyzed. A diagnostic model was constructed using stepwise regression, and experimental verification was conducted on alpha-Tocomonoenol, one of the key differential metabolites. Additionally, the effect of alpha-Tocomonoenol on cell proliferation was evaluated in LNCaP, 22Rv1, and RWPE-1 cells.ResultsSix differential metabolites between the prostate cancer group and the benign prostatic hyperplasia group were used to construct a diagnostic model, which showed a high area under the curve (AUC = 0.9433). Experimental verification revealed that alpha-Tocomonoenol inhibited the proliferation of LNCaP and 22Rv1 cells by binding to androgen receptors, while it had no significant effect on the proliferation of RWPE-1 cells.DiscussionThis study demonstrates that serum metabolites have the potential to serve as diagnostic biomarkers for the early detection of prostate cancer. Furthermore, alpha-Tocomonoenol might exert an anti-proliferative effect on prostate cancer cells through binding to androgen receptors, providing new insights into the development of novel diagnostic tools and therapeutic strategies for prostate cancer.